POTENTIAL OF CHITOSAN IN REDUCING GA3 DOSES AND THEIR EFFECT ON GROWTH, YIELD, AND BULB QUALITY IN “GIZA RED” ONION - A.H. Roshdy; A. A. Khadr (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Tow field experiments were conducted during the seasons of 2020/2021 and 2021/2022 at the experimental farm Etay El-Baroud research station to investigate the effect of foliar application with gibberellic acid (GA3) at 50 and 100 ppm and the chitosan (CS) at of 100 and 200 ppm, in addition, to control for each to Giza Red onion. The results showed significant and positive effects of the examined concentrations of GA3 or CS on all the studied characters except leaves number and shape index, in both seasons. Concerning the interaction effect, all of the studied characters were enhanced significantly in all treatment combinations between GA3 and CS levels. The treatments of GA3 (50 ppm) with CS (200 ppm), GA3 (100 ppm) with CS (100 ppm), and GA3 (100 ppm) with CS (200 ppm) were found to give the highest mean values for all characters, in both seasons without significant differences among them. Also, the results revealed some kind of synergistic effect between GA3 and CS where the combined application was found to be more effective in onion plants performance thane the single ones that gave the ability to reduce the used doses of GA3 by 50%, which, consequently, reduce the expected hazardous of using gibberellins.